Réponses

2014-02-26T01:43:46+01:00
N°47 a) (2x+3)² +(2x+3)(5x-1) =(2x+3)(2x+3+5x-1)
                                                = (2x+3) ( 7x +2)
             résoudre l'équation : (2x+3)(7x+2)=0
                                               ab=0 si et seulement si a=0 ou b=0 
                                               2x+3=0    7x+2=0
                                               x= -3/2       x= -2/7  S={ -3/2 ; -2/7}

          b) (x-2)² -(4x+9)(x-2) = (x-2) ( x-2 -4x -9)
                                            = (x -2) ( -3x -11)
              Résoudre l'équation : (x-2)(-3x-11)=0
                                                ab= 0 si et seulement si a=0 ou b=0
                                                 x -2 = 0        -3x-11=0
                                                 x =2                x= -11/3   S = { 2 ; -11/3}            

n° 50 a) E = (4x-5)(x-2) -x(x+4)
                 = 4x² -8x +5x -10 -x² -4x
                 = 3x² -7x -10
             
              F = (3x-10)(x-1)
                 = 3x² +3x -10x -10
                = 3x² -7x -10


Donc E= F